3D compositional analysis at atomic scale of InAlGaAs capped InAs/GaAs QDs. (1st July 2015) - Hernández-Saz, J.; Herrera, M.; Molina, S.I.; Stanley, C.R.; Duguay, S.
Graphical abstract: Abstract : The 3D compositional distribution at the atomic-scale of InAs/GaAs quantum dots (QDs) with an InAlGaAs capping layer has been obtained by atom probe tomography. A heterogeneous distribution of Al atoms has been revealed. An Al-rich ring around the QDs has been observed. A detailed analysis of the QDs composition evidences a high degree of In/Ga intermixing, with an increasing In gradient in the growth direction. The atomic scale analyses of these nanostructures are essential to understand their functional properties.